Manajemen Dakwah Berbasis Kearifan Lokal: Studi Komunitas Nelayan dan Petani Pesisir Indragiri Hilir - Al Kahfi (UIN Raden Mas Said Surakarta, 2026)
This study examines da'wah management among coastal fishing and farming communities in Enok Subdistrict, Indragiri Hilir Regency, Riau, a predominantly Muslim area that nonetheless faces a gap between religious identity and the depth of Islamic practice, driven by geographic isolation, mismatched da'wah scheduling, a shortage of preachers, and limited local-wisdom-based approaches. This research analyzes the da'wah management strategies employed by preachers and local religious institutions in reaching these communities. This qualitative case study used in-depth interviews, participatory observation, and documentation. Findings show that of the four da'wah management functions, three operate consistently: planning adapted to fishing and farming rhythms, actuating through da'wah bil-hal and cultural da'wah rooted in Malay local wisdom, and participatory organizing involving local community leaders. Mosques, surau, and majelis taklim serve as the core da'wah infrastructure, with women's majelis taklim acting as a bridge transmitting Islamic values to male farmers who are hardest to reach due to prolonged stays at remote plantations. The annual Musabaqah Tilawatil Qur'an (MTQ) proves to be the most effective instrument for religious mobilization. Meanwhile, the controlling function remains unsystematic. This study recommends proactive, outreach-based innovations in da'wah management as a model for da'wah programs in other coastal and agrarian regions of Indonesia.